Peranan Kepolisian Resor Pelalawan Dalam Upaya Penegakan Hukum Kebakaran Lahan Di Wilayah Hukum Pelalawan - Rudi Lesmono; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Pelalawan is a Regency in the Province of Riau. Pelalawan Regency became one of experiencing forest fire and land large enough that cause a lot of harm to the public good material as well as immaterial. The purpose of writing this legal scription, namely; First to know the crime investigation of land by burning the resort of Pelalawan Police, Secondly, to know the obstacles in the crime investigation of land by burning the Resort of Pelalawan Police, Third, to find out the efforts made to overcome the obstacles in the investigation of criminal acts of burning relic within the territory of law of the Resort of Pelalawan Police.This type of research can be classified into types of juridical sociological research, because in this study the authors direct research on the location or place of observed in order to give a complete and clear picture of the problems examined. This research was conducted in the territory of law of the Resort of Pelalawan Police, while population and sample was a whole party that deals with issues that are examined in this study, the data sources used, the primary and secondary data are data which consists of primary legal materials, secondary and tertiary, data collecting techniques in this study with a questionnaire, depth interviews and library studies.From the results of the research there are three basic issues that can be inferred. First, the investigation of criminal acts of burning land by the Resort of Pelalawan Police hasn't been fullest. Second, Barriers encountered in the investigation of criminal acts of burning land by the Resort of Pelalawan Police derived from topographic factors/geographic, operational budget and transportation factors, factors of community participation. Third, efforts are being made to overcome the obstacles in the investigation of criminal acts of burning land by the Resort of pelalawan Police is by means of Dissemination of legislation related to the prevention of the crime of burning land, place personnel of the Resort of Pelalawan Police in every village to be considered vulnerable would be the occurrence of forest fires and land, establishing cross-cutting cooperation with local governments of Pelalawan Hilirspida by forming a warkabel unit of burning land community care i.e. community care Fire.The author's suggestion, first, the need for synergy between law enforcement agencies in tackling and eradicating the crime of burning land in the legal territory of the Resort of Pelalawan Police. Secondly, the operational budget of the plotting disaster mitigation forest fires and land in State income and Expenditure Budget (APBN) as well as Region Budgetary income and Expenditure (APBD), and improving the quality and quantity of the means and infrastructure support. Third, institutional coordination (agencies) are cross-cutting, a commitment between the Central Government and Local governments, and to all elements of society in order to have concern and play an active role in the protection and management of the environment.Kata Kunci : Penyidikan – Tindak Pidana - Pembakaran Lahan